Lakhpati Kisan: Transforming Agriculture-Based Livelihoods for Smallholder Farmers in India (Public Policy in India, 2025)
Agriculture plays an essential role in the growth of developing economies, as agricultural production is key to food security and is closely intertwined with the livelihoods of many. This book explores the lives of smallholder agricultural farmers in India and the dire challenges that agricultural households face. Focussing on the Lakhpati Farmers initiative, the book examines interventions made by the programme to economically empower farmers and accelerate income growth in the agriculture sector. The programme, initiated by the Collectives for Integrated Livelihood Initiatives (CInI) in the tribal belts of central Indian states, helped farmers earn over INR 100,000 (or one lakh – hence Lakhpati) per annum. The programme engaged with households in 12 districts across 4 states – Jharkhand, Odisha, Maharashtra, and Gujarat – to bring about change through economic empowerment and improve the quality of life of tribal communities. This book documents these initiatives and strategies to meet the aspirations of small and marginal farmers by understanding the ingredients, processes, and challenges involved. The book analyses the programme, examines case studies, and offers ways forward. Part of the Innovations, Practice and the Future of Public Policy in India series, this volume will interest students and researchers of agriculture and rural development, business management, governance, public policy, development studies, and sociology. This book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons (CC-BY-NC-ND) 4.0 license.